EFL Teachers Lived Experience in Teaching English to Young Learners: Exploration Study of Legend Private English Course - Fahrul Rozi (Universitas Ahmad Dahlan, 2022)
Lived experience refers to a representation of experiences and choices of a given person and knowledge gained from all individuals’ experiences involved on their work. Teaching English to young learners (TEYL) might be quite difficult to face as every English teacher should be able to deal with variety of their characters and learning interest towards English. Besides, every English teacher who had taught for years could gain more experiences in teaching the students dealing with the issues occurred. The researcher, therefore, was interested in exploring EFL teachers’ lived experiences in TEYL based on the mentioned phenomena. In addition to answer the research questions, this research